Portable pineapple quality nondestructive testing equipment - FAN CHANGXIANG; WU ZHAOCHENG; XU SAI; LIANG XIN; LU HUAZHONG; QIU GUANGJUN; QIN JINZHUAN; WU RUHUI; CHEN MINGWEN (2024)
The utility model discloses portable pineapple quality nondestructive testing equipment which comprises a machine shell, a first partition plate, a second partition plate and a third partition plate are fixedly connected between the top and the bottom of the inner wall of the machine shell, and an inner cavity of the machine shell is divided into a first equipment cavity, a testing chamber and a second equipment cavity through the first partition plate, the second partition plate and the third partition plate. And a detection port communicated with the detection chamber is formed in the front surface of the shell. The adjusting handle is rotated to drive the two-way lead screw to rotate, the two threaded blocks can be driven to move towards the opposite side or the separated side, then the wedge-shaped placing base can be driven to ascend or descend through the connecting rod, and the height of the wedge-shaped placing base and the height of a pineapple sample placed on the top of the wedge-shaped placing bas